Efficacy and predictors of short-term first-generation somatostatin analog presurgical treatment in acromegaly: A hospital-based study of 237 cases. (December 2020) - Shen, Ming; Yang, Yeping; He, Wenqiang; Qiao, Nidan; He, Min; Shou, Xuefei; Wang, Meng; Ma, Zengyi; Ye, Zhao; Zhang, Yichao; Chen, Zhengyuan; Zhang, Qilin; et al.
Abstract: Objective: To investigate the effectiveness and predictors of short-term somatostatin analog (SSA) presurgical therapy in a large cohort and to assess the correlation between clinical and pathological variables. Design: 237 newly diagnosed patients with acromegaly received presurgical SSA treatment for three months were recruited. Clinical characteristics were collected, and response to SSA in hormone and tumor size was evaluated. The correlation between clinical information and pathological variables were analyzed. Results: After 3 months presurgical SSA therapy, 51 (21.5%) patients were biochemically responsive with ≥50% decrease in IGF-1 while 126 (53.2%) patients showed at least 20% tumor size decrease. Biochemical responders were associated with a smaller maximum tumor diameter (MTD) and an older age (OR, 0.448; P = 0.003; OR, 1.050; P = 0.001). Tumor size responders were associated with a smaller MTD (OR, 0.435; P < 0.001). A combination of MTD < 2 cm and age ≥49 years predicted biochemical responders (PPV, 54.5%; NPV, 86.0%; P < 0.001), while MTD ≤2.2 cm (PPV, 67.1%; NPV, 67.0%; P < 0.001) predicted tumor size responders. Compared to patients with MTD < 2 cm, patients with MTD ≥ 2 cm showed higher percentage of sparsely granulated (SG) adenoma (62.1% vs. 31.3%, P = 0.005). In addition, the percentage of SG adenoma tended to be higher in patients < 49 years than ≥49 years (48.1% and 31.0% P = 0.089). Conclusions: The baseline MTD and age correlate with granulation patterns and may be used as easily acquired predictors of presurgical SSA treatment in acromegaly. Patients over their 50s with a tumor less than 2 cm in diameter are more likely to have a response to the short-term presurgical SSA therapy. Highlights: The biochemical response rate after short-term SSA presurgical therapy is 20%. The tumor size response rate after short-term SSA presurgical therapy is 50%. Tumor diameter and age predict the efficacy of short-term SSA presurgical therapy. Tumor diameter and age correlate with its granulation patterns and Ki-67 index. Patients over 50s with a tumor < 2 cm are more likely to have a response to SSA.